Deletion of spoIIAB blocks endospore formation in Bacillus subtilis at an early stage. - Coppolecchia, R (1991)
During an early stage of endospore formation in Bacillus subtilis, the cell divides asymmetrically into two compartments that follow different developmental paths. The differential expression of genes in these two compartments is controlled in part by the production of compartment-specific transcription factors, sigma G and sigma K. It is not known how sigma G accumulation is restricted to one of the two compartments, the forespore. However, the observations that sigma F directs transcription of the structural gene for sigma G and that sigma F activity can be modified by the product of a gene, spoIIAB, has led us to investigate the role of spoIIAB during sporulation. We have isolated mutants that carry deletion alleles of spoIIAB. Electron microscopic examination of these mutants revealed that these mutations blocked endospore formation at an early stage before septation and caused extensive cell lysis. The spoIIAB deletion alleles caused hyperexpression of genes that are normally expressed exclusively in the forespore compartments of sporulating wild-type cells, whereas these alleles reduced expression of other genes, including spoIIE, which is expressed before septation in wild-type cells. These observations confirm that spoIIAB is essential for sporulation and are consistent with models in which the product of spoIIAB plays a role in regulating the timing and/or compartment specificity of sigma F- and sigma G-directed transcription.